Novel function of the endoplasmic reticulum degradation‐enhancing α‐mannosidase‐like proteins in the human hepatitis B virus life cycle, mediated by the middle envelope protein. (23rd September 2016) - Lazar, Catalin; Uta, Mihaela; Petrescu, Stefana Maria; Branza‐Nichita, Norica
Abstract: Cells replicating the human hepatitis B virus (HBV) express high levels of degradation‐enhancing α‐mannosidase‐like proteins (EDEMs), a family of proteins involved in the endoplasmic reticulum associated degradation, one of the pathways activated during the unfolded protein response. Owing to their α‐1, 2 mannosidase activity, the EDEM1–3 proteins are able to process the N‐linked glycans of misfolded or incompletely folded proteins, providing the recognition signal for their subsequent degradation. The HBV small (S), medium (M), and large (L) surface proteins bear an N‐linked glycosylation site in the common S domain that is partially occupied in all proteins. The M protein contains an additional site in its preS2 domain, which is always functional. Here, we report that these oligosaccharides are processed by EDEMs, more efficiently by EDEM3, which induces degradation of L and S proteins, accompanied by a reduction of subviral particles production. In striking contrast, M not only is spared from degradation but its trafficking is also accelerated leading to an improved secretion. This unusual behavior of the M protein requires strictly the mannose trimming of the preS2 N‐linked glycan. Furthermore, we show that HBV secretion is significantly inhibited under strong endoplasmic reticulum stress conditions when M expression is prevented by mutagenesis of the viral genome. These observations unfold unique properties of the M protein in the HBV life cycle during unfolded protein response and point to alternative mechanisms employed by EDEMs to alleviate this stress in case of necessity by promoting glycoprotein trafficking rather than degradation.